Association between autism spectrum disorder and inflammatory bowel disease: A systematic review and meta‐analysis. Issue 2 (23rd December 2021) - Kim, Jong Yeob; Choi, Min Je; Ha, Sungji; Hwang, Jimin; Koyanagi, Ai; Dragioti, Elena; Radua, Joaquim; Smith, Lee; Jacob, Louis; de Pablo, Gonzalo Salazar; Lee, Seung Won; Yon, Dong Keon; et al.
Abstract: Children with autism spectrum disorder (ASD) are frequently diagnosed with co‐occurring medical conditions including inflammatory bowel disease (IBD). To investigate the association, we conducted a systematic review registered in PROSPERO (ID:CRD42021236263) with a random‐effects meta‐analysis. We searched PubMed, Embase, and PsycInfo (last search on January 25, 2021), and manually searched relevant publications. We included observational studies measuring the association between ASD and IBD. The primary outcome was the association (odds ratio, OR) between ASD and later development of IBD. Sensitivity analyses were conducted by quality, confounding adjustment, and study design. We performed meta‐regression analyses and assessed heterogeneity, publication bias, and quality of studies with the Newcastle‐Ottawa Scale. Overall, we included six studies consisting of eight datasets, including over 11 million participants. We found that ASD was significantly associated with subsequent incident IBD (any IBD, OR = 1.66, 95% confidence interval[CI] = 1.25–2.21, p  < 0.001; ulcerative colitis, OR = 1.91, 95%CI = 1.41–2.6, p  < 0.001; Crohn's disease, OR = 1.47, 95%CI = 1.15–1.88, p =  0.002). ASD and IBD were also associated regardless of temporal sequence of diagnosis (any IBD, OR = 1.57, 95%CI = 1.28–1.93, p  < 0.001; ulcerative colitis, OR = 1.7, 95%CI = 1.36–2.12, p  < 0.001; Crohn's disease, OR = 1.37, 95%CI = 1.12–1.69, p =  0.003). Sensitivity analyses confirmed the findings of the main analysis. Meta‐regression did not identify any significant moderators. Publication bias was not detected. Quality was high in four datasets and medium in four. In conclusion, our findings highlight the need to screen for IBD in individuals with ASD, and future research should identify who, among those with ASD, has the highest risk of IBD, and elucidate the shared biological mechanisms between ASD and IBD. Lay Summary: This systematic review and meta‐analysis of eight observational datasets found that individuals with autism spectrum disorder (ASD) are more likely to develop any inflammatory bowel disease, ulcerative colitis, or Crohn's disease. Our findings highlight the need to screen for inflammatory bowel disease in patients with ASD and elucidate the shared biological mechanisms between the two disorders.